Immunodetection of cells with a CD44+/CD24-phenotype in canine mammary neoplasms - Magalhaes, Georgia Mode [UNESP]; Terra, Erika Maria [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP]; Bandarra, Marcio de Barros [UNESP]; Reina Moreira, Pamela Rodrigues [UNESP]; Rosolem, Mayara Caroline [UNESP]; Alessi, Antonio Carlos [UNESP] (Biomed Central Ltd., 2013)
Background: Cancer stem cells (CSCs) are able to self-renew and to form metastases. Using flow cytometry, CSCs were detected in canine mammary tumors as cells CD44(+) and CD24(-). The aim of this study was to detect these CSCs by immunohistochemistry and correlate their frequency with canine mammary neoplasm grade and histopathological type. 130 mammary neoplasm samples were selected from tissue blocks at the Department of Pathology at UNESP and classified according to (BJVP 4:153-180, 2011). These samples were composed by adenomas, lymph node metastases, solid carcinomas grades II and III, tubular, papillary and carcinomas in mixed tumor grades I, II and III. Immunohistochemistry was performed with antibodies against CD44 and CD24. Linear regression was performed using Pearson's correlation test.Results: The value at CD44 was positive and CD24 becomes zero was 46.75%. Cells with a CD44(+)/CD24(-) phenotype were detected in 40 out of 130 samples with an advantage of high grade tumors (II and III) and metastases among tubular, papillary and carcinomas in mixed tumors. In these samples, percentages of cells stained by CD44 and CD24 antibodies were 62.2% and 0%, respectively. Published reports usually correlate grade III tumors with the expression of CD44 but not with CD24 expression. Studies using flow cytometry have found CSC frequencies similar to those found in our study.Conclusions: Immunohistochemistry was found to be a reliable technique for the detection of CSCs in canine mammary neoplasms, and the frequency of these cells positively correlates with grades II and III tumors (poor prognosis).
Keywords: Cancer stem cells; CD44; CD24; Canine neoplasia; Oncology; Mammary neoplasia; Canine; Stem cell